Towed array plane and non-planewave beamforming under ship's maneuvering - Felisberto, P. (2014)
Towed hydrophone arrays are commonly used for determining the spatial characteristics of the underwater acoustic field. The assumptiont that the hydrophones lie in a straight and horizontal line is often made when beamforming the hydrophones outputs.